An Analysis Of The Education Loan Scheme's Growth And Performance In The Financial Industry In Haryana (International Journal of Environmental Sciences, 2025)
This research provides an analysis of the dynamics and effectiveness of education loan schemes in Haryana's banking sector. It discusses key aspects like disbursement of loans, balance outstanding, non-performing assets (NPAs), and recovery ratios in both public and private sector banks. The research highlights the challenges. Add high default rates, limited access in distant areas, and concerns over financial viability. Secondary data were used to examine the expansion and performance of the education loan scheme. The study shows that the use of technology and policy reforms is critical to improving the accessibility of loans and recovery, thereby providing for the sustainability of education loan schemes.